Biodiversity facets affect community surface temperature via 3D canopy structure in grassland communities. (9th March 2021) - Guimarães‐Steinicke, Claudia; Weigelt, Alexandra; Proulx, Raphaël; Lanners, Thomas; Eisenhauer, Nico; Duque‐Lazo, Joaquín; Reu, Björn; Roscher, Christiane; Wagg, Cameron; Buchmann, Nina; Wirth, Christian
Abstract: Canopy structure is an important driver of the energy budget of grassland ecosystem and is, at the same time, altered by plant diversity. Diverse plant communities typically have taller and more densely packed canopies than less diverse communities. With this, they absorb more radiation, have a higher transpiring leaf surface and are better coupled to the atmosphere which leads to cooler canopy surfaces. However, whether plant diversity generally translates into a cooling potential remains unclear and lacks empirical evidence. Here, we assessed how functional identity, functional diversity and species richness of grassland communities in the Jena Experiment predict the mean and variation of plant surface temperature mediated via effects of canopy structure. Using terrestrial laser scanning, we estimated canopy structure describing metrics of vertical structure (mean height, LAI), the distribution (evenness) and the highest allocation (centre of gravity) of biomass along height strata. As metrics of horizontal structure, we considered community stand gaps, canopy surface variation and emergent flowers. We measured surface temperature with a thermal camera. We used SEM models to predict biodiversity effects on the surface temperature during two seasonal peaks of biomass. Before the first cut in May, herb‐dominated communities directly promoted lower leaf surface temperatures. However, communities with lower centre of gravity (mostly herb dominated) also increased canopy surface temperatures compared with grass‐dominated communities with higher biomass stored in the top canopy. Grass‐dominated communities showed a smaller variation of surface temperatures, which was also positively affected by species richness via an increase in mean height. In August, mean surface temperature decreased with increasing community CC and LAI. The variation of surface temperature was greater in herb‐dominated than in grass‐dominated communities and increased with plant species richness (direct effects). Synthesis . The mean and variation of canopy surface temperature were driven by differences in functional group composition (herbs‐ vs. grass dominance) and to a lesser extent by plant diversity. These effects were partly mediated the metrics of canopy structure but also by direct effects unrelated to the structural metrics considered. Abstract : The mean and variation of canopy surface temperature were driven by differences in functional group composition (herbs‐ vs. grass dominance) and to a lesser extent by plant diversity. These effects were partly mediated the metrics of canopy structure but also by direct effects unrelated to the structural metrics considered.